2008
DOI: 10.1038/nn.2109
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity patterns predict speech discrimination ability

Abstract: Neural activity in the cerebral cortex can explain many aspects of sensory perception. Extensive psychophysical and neurophysiological studies of visual motion and vibrotactile processing show that the firing rate of cortical neurons averaged across 50-500 ms is well correlated with discrimination ability. In this study, we tested the hypothesis that primary auditory cortex (A1) neurons use temporal precision on the order of 1-10 ms to represent speech sounds shifted into the rat hearing range. Neural discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
350
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(405 citation statements)
references
References 50 publications
(47 reference statements)
53
350
2
Order By: Relevance
“…The decoding performance was best when short time bins were used to sample the response, revealing that the temporal structure of the neurons responses (not just the response magnitude) provides information to distinguish individual sounds. In this respect, insula neurons resemble those found in auditory cortex (Schnupp et al, 2006;Engineer et al, 2008).…”
Section: Selectivity To Individual Vocalizationssupporting
confidence: 52%
“…The decoding performance was best when short time bins were used to sample the response, revealing that the temporal structure of the neurons responses (not just the response magnitude) provides information to distinguish individual sounds. In this respect, insula neurons resemble those found in auditory cortex (Schnupp et al, 2006;Engineer et al, 2008).…”
Section: Selectivity To Individual Vocalizationssupporting
confidence: 52%
“…For example, trained rats were shown to being able to report millisecond differences in patterns of electrical microstimulation applied to auditory cortex (31), demonstrating that auditory cortex can access temporally precise patterns of local activity. In addition, another study demonstrated that behavioral performance can be better explained when decoding neural population activity sampled at a precision well below 10 ms than when decoding the same responses at coarser time scales (32). The present results demonstrate that the responses of individual neurons can indeed contribute to such millisecond encoding of complex sounds.…”
Section: Discussionmentioning
confidence: 50%
“…Although we cannot conclude that the neurophysiological response properties we have described here are necessarily essential for behavior, several existing studies using synthetic stimuli (34) and speech (23) have demonstrated that ferrets and rodents are able to perceive target sounds in noisy conditions similar to those used in this study. The functional properties observed for speech and conspecific vocalizations in distorted conditions may reflect computational strategies used in these behaviors, and future studies that combine our unique computational approach and behavior paradigms promise valuable new insight into the general problem of identifying signals in the background of interfering sources (5).…”
Section: Discussionmentioning
confidence: 65%
“…Their robust representations in neural data are therefore crucial for speech comprehension. As with other natural sounds, it is likely that basic neural mechanisms contribute to the stability and robustness of their representations in early stages of auditory processing (23). To examine the effect of distortions on phoneme category representation, we measured the mean phoneme spectrograms averaged over all of the instances of individual phonemes (24).…”
Section: Reduced Distortions In Stimuli Reconstructed From the A1 Popmentioning
confidence: 99%